Tumor Testing for Somatic and Germline BRCA1/BRCA2 Variants in Ovarian Cancer Patients in the Context of Strong Founder Effects - Peixoto, Ana; Pinto, Pedro; Guerra, Joana; Pinheiro, Manuela; Santos, Catarina; Pinto, Carla; Santos, Rui; Escudeiro, Carla; Bartosch, Carla; Canário, Rita; Barbosa, Ana; Gouveia, Alfredo; et al. (Frontiers in Oncology, 2020)
Deleterious variants in the BRCA1/BRCA2 genes and homologous recombination deficiency (HRD) status are considered strong predictors of response to poly (ADP-ribose) polymerase (PARP) inhibitors (PARPi). The introduction of PARPi in clinical practice for the treatment of patients with advanced ovarian cancer imposed changes in the molecular diagnosis of BRCA1/BRCA2 variants. BRCA1/BRCA2 tumor testing by next-generation sequencing (NGS) can detect simultaneously both somatic and germline variants, allowing the identification of a higher number of patients who may benefit from PARPi. Our main goal was to determine the frequency of somatic and germline BRCA1/BRCA2 variants in a series of non-mucinous OC, and to define the best strategy to be implemented in a routine diagnostic setting for the screening of germline/somatic variants in these genes, including the BRCA2 c.156_157insAlu Portuguese founder variant. We observed a frequency of 17.8% of deleterious variants, 12.6% germline and 5.2% somatic. A higher prevalence of pathogenic variants was observed in patients diagnosed with high-grade serous ovarian cancer (21.1%). Considering the frequencies of the c.3331_3334del and the c.2037delinsCC BRCA1 variants observed in this study (73% of all BRCA1 pathogenic germline variants identified) and the limitations of NGS to detect the BRCA2 c.156_157insAlu variant, it might be cost-effective to test for these founder variants with a specific test prior to tumor screening of the entire coding regions of BRCA1 and BRCA2 by NGS in patients of Portuguese ancestry.